2022
DOI: 10.1177/08901171221137056
|View full text |Cite
|
Sign up to set email alerts
|

Can United States Adults Accurately Assess Their Diet Quality?

Abstract: Purpose To estimate the percentage of United States adults who accurately assessed their diet quality (DQ). Design Observational, cross-sectional, nationally representative. Setting National Health and Nutrition Examination Survey, 2015-2018. Sample 9757 (86%) of 11 288 adults aged ≥20 years. Measures Perceived DQ was assessed by asking participants, how healthy is your diet? The five responses included excellent, very good, good, fair, and poor. Measured DQ was assessed using 24-hours dietary recalls scored w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The inconsistent results observed in previous studies could be attributed to differences in demographics, sample sizes, and factors considered in the analysis. [ 27 ] For instance, recent studies have highlighted the importance of distinguishing between populations with varying BMIs in epidemiological research on osteoporosis. [ 28 , 29 ] However, many studies have employed statistical analyses that treat all populations equally, leading to potentially misleading results.…”
Section: Discussionmentioning
confidence: 99%
“…The inconsistent results observed in previous studies could be attributed to differences in demographics, sample sizes, and factors considered in the analysis. [ 27 ] For instance, recent studies have highlighted the importance of distinguishing between populations with varying BMIs in epidemiological research on osteoporosis. [ 28 , 29 ] However, many studies have employed statistical analyses that treat all populations equally, leading to potentially misleading results.…”
Section: Discussionmentioning
confidence: 99%
“…38 Many sociodemographic, clinical and dietary factors might contribute to these misperceptions of dietary quality. 35 In Xue et al's study, each 10-year increase in age was associated with greater odds of being incorrectly optimistic about dietary quality, 38 while different age groups had a differential effect on being incorrectly optimistic in Variyam et al's study of the general population. 36 While there are only few studies examining predictors of misperceptions of dietary quality, 36,38 previous research is inconclusive regarding associations between dietary quality perception (whether correct or not) and demographic factors such as age [38][39][40][41] and sex.…”
Section: Introductionmentioning
confidence: 95%
“…33,34 This misperception is exhibited in the general population, 35,36 and in clinical populations, including people LWBC 37,38 and may mean that individuals do not believe in, nor identify a need to, improve their diet. 34,35 This has been observed in a nationally representative sample of people LWBC where Xue et al reported low conformance between perceived and actual dietary quality, with 56% of participants being categorised as incorrectly optimistic about their diets. 38 Many sociodemographic, clinical and dietary factors might contribute to these misperceptions of dietary quality.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations